Dixie's daughters : the United Daughters of the Confederacy and the preservation of Confederate culture - Cox, Karen L., 1962- (New perspectives on the history of the South., 2003)
''A vital and, until now, missing piece to the puzzle of the 'Lost Cause' ideology and its impact on the daily lives of post-Civil War southerners. This is a careful, insightful examination of the role women played in shaping the perceptions of two generations of southerners, not simply through rhetoric but through the creation of a remarkably effective organization whose leadership influenced the teaching of history in the schools, created a landscape of monuments that honored the Confederate dead, and provided assistance to elderly veterans, their widows, and their children."